Ist das Angebot von Nahrungsmitteln "Ohne Gentechnik" wirtschaftlich nachhaltig? - Thomas Venus; Nicholas Kalaitzandonakes; Justus Wesseler (Vierteljahrshefte zur Wirtschaftsforschung, 2012)
In diesem Beitrag wird diskutiert, ob das Angebot von Nahrungsmitteln mit der Kennzeichnung "Ohne Gentechnik" wirtschaftlich nachhaltig ist. Zudem wird dem Leser ein Überblick gegeben zur Regulierung genetisch veränderter Organismen (GVO) in der EU und zur Entwicklung der Kennzeichnungen "Ohne Gentechnik" oder "gentechnikfrei" in EU-Mitgliedsstaaten. Dies wird vor allem vor dem Hintergrund steigender Risiken durch "asynchrone Zulassungsprozesse" und "Low-Level Presence" von GVO diskutiert. – – This article discusses to the evaluation of the economic sustainability of genetically modified free, "GM-free", product labeling. The rules and regulations governing the "GM-free" product label in the European Union are discussed in detail. The major question we address is whether the supply of "GM-free" labelled animal products can be an economically sustainable strategy. We discuss this question against the backdrop of emerging supply chain risks caused by low-level presence (LLP) of unapproved GM organisms (GMOs) as well as the asynchronous approval of GMOs.
Keywords: K13; O33; Q13; Q16; Q18; 330; Consumer welfare; genetically modified organisms; labeling; producer welfare; regulation